Strength/power augmentation subsequent to short-term training abstinence - Weiss, L. W.; Wood, L. E.; Fry, A. C.; Kreider, R. B.; Relyea, G. E.; Bullen, D. B.; Grindstaff, P. D. (The Journal of Strength and Conditioning Research, 2004)
Strength augmentation has been demonstrated in resistance-trained men subsequent to 4 days of training abstinence. However, this phenomenon was exhibited in an unusual circumstance in which the exercise test (seated heel raise) primarily involved an isolated skeletal muscle (soleus) that is normally comprised almost exclusively of 1 fiber type. It is unclear if similar results would be found for aggregate muscle actions. Therefore, a comparable study was designed with this in mind. Subjects were apparently healthy, young, strength-trained men (n = 25). All performed various tests of bench press strength at the beginning of their last standardized dynamic constant external resistance (DCER) training session. Subjects were subsequently randomly assigned to 1 of 4 groups and repeated the identical tests at intervals of either 2, 3, 4, or 5 days with no intervening training. Strength tests consisted of 1 repetition maximum (1RM) concentric-only isokinetic bench presses performed at 1.49 and 0.37 m·s-1 as well as a 1RM DCER bench press. Measures of peak force and power were obtained from the isokinetic tests and maximum load from the DCER test. Results were expressed in both absolute and relative (to body weight) terms. Subsequent to the 4 abstinence intervals, groups performed similarly (p > 0.05) for all dependent variables. Concurrently, however, a small effect size (ES) was found for the group having a 4-day respite for both absolute and relative expressions of peak force and power at the slowest isokinetic bench press velocity. A small ES was also identified for the group having 2 days of rest for relative peak force at the slowest isokinetic test velocity and for relative DCER strength. Therefore, modest and transient strength augmentation appears likely in aggregate muscle actions following 2-4 days of training abstinence in resistance-trained men, but only at relatively slow velocities.